From the Pen to the Prompt: Scientific Authorship in the Shadow of AI. Who Thinks? Who Signs? - Agbocou, Jules Clotaire K.; Islam, Mohammad Shahidul (Transactions on Engineering and Computing Sciences, 2025)
This paper explores the redefinition of scientific authorship in the era of generativeartificial intelligence (GAI). Drawing on a reflexive approach, the study analyzes the impact of GAI on scientific creation processes while examining concerns about the dilution of intellectual responsibility. Through a literature review and an examination of current practices in academic settings, the author demonstrates that GAI does not eliminate human authorship but transforms it by offering new forms of collaboration between humans and machines. The main findings highlight the need to redefine scientific authorship by emphasizing intellectual intentionality and human responsibility, while integrating GAI as a tool for creative support.